Activities of Encyclopedic Educator and Intellectual Culture of 18th Century - S. A. Gerasimova (Научный диалог)
The article is devoted to the issues of reflection of the intellectual culture of the Enlightenment in popular science discourse, represented in the activities of encyclopedic educators. The relevance of the research topic is due to the study of the views of the scientist, which influenced the value coordinates of popular science knowledge of the society of that time. The research methodology is based on a narrative approach in a historiographic perspective, as well as a culture-anthropocentric method that reveals the biography of a scientist as a manifestation of the socio-cultural processes of the era. The use of these methods determined the novelty of the research as a vector of movement of research thought, modeling the phenomenon of professionalism, since it contributes to a deeper understanding of the specifics of the professional picture of the scientist’s world. The dynamics of the views of the French educator Louis de Jaucourt is revealed, the degree of his contribution to the formation of the French Encyclopedia (Encyclopédie, ou Dictionnaire raisonné des sciences, des arts et des métiers) is determined. It is proved that moral satisfaction from participation in the creation of an encyclopedia, due to the creativity of his personality, has become significant for the scientist. The research material was the articles by L. de Jaucourt posted on the website of the first edition of the encyclopedia. Analysis of the articles shows that their pragmatics are aimed at trans-mitting information to an educated reader in popular science discourse.